KEBIJAKAN AUSTRALIA DALAM MENGATASI ILLEGAL IMMIGRANT DI BAWAH PEMERINTAHAN PM TONY ABBOTT (Australia Policy to Solve Problem of Illegal Immigrant Under the Government of Tony Abbott) - Taufik Eko Hidayanto (HI 16 UMY 145, 2016)
*145 This paper describes about Australia’s policy to control the illegal immigrants under the government of Prime Minister Tony Abbott. Australia is one of the destination countries for illegal immigrants who escaped from several countries for the purpose to obtaining an asylum. The increased arrivals of illegal immigrants from year to year make impact to sovereignty and security of Australia region. Therefore, it requires the government to be firm in handling it. The policy that is adopted by Prime Minister Tony Abbott to control the arrival of illegal immigrants is Operation Sovereign Borders (OSB) policy. OSB is done by placing Australian military in border area to prevent the arrival of illegal immigrants or asylum seeker by boat.